Dietary influence on modulation of Helicoverpa armigera oral secretion composition leading to differential regulation of tomato plant defense - Gopal S. Kallure; Balkrishna A. Shinde; Vitthal T. Barvkar; Archana Kumari; Ashok P. Giri (Plant Science, 2022)
Little is known about how different plant-based diets influence the insect herbivores’ oral secretion (OS) composition and eventually the plant defense responses. We analyzed the OS composition of the generalist Lepidopteran insect, Helicoverpa armigera feeding on the host plant tomato (OSH), non-host plant capsicum (OSNH), and artificial diet (OSAD) using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Higher numbers and levels of alkaloids and terpenoids were observed in OSH and OSNH, respectively while OSAD was rich in phospholipids. Interestingly, treatment of H. armigera OSAD, OSH and OSNH on wounded tomato leaves showed differential expression of (i) genes involved in JA and SA biosynthesis and their responsive genes, and (ii) biosynthetic pathway genes of chlorogenic acid (CGA) and trehalose, which exhibited increased accumulation along with several other plant defensive metabolites. Specifically, high levels of CGA were detected after OSH and OSNH treatments in tomato leaves. There was higher expression of the genes involved in phenylpropanoid biosynthesis, which may lead to the increased accumulation of CGA and related metabolites. In the insect bioassay, CGA significantly inhibited H. armigera larval growth. Our results underline the differential accumulation of plant and insect OS metabolites and identified potential plant metabolite(s) affecting insect growth and development.
Keywords: Chlorogenic acid; defense; Metabolites; Non-host; Oral secretion; trehalose

Dietary influence on modulation of Helicoverpa armigera oral secretion composition leading to differential regulation of tomato plant defense. - Kallure, Gopal S.; Shinde, Balkrishna A.; Barvkar, Vitthal T.; Kumari, Archana; Giri, Ashok P. (Plant Science, 2022)
Little is known about how different plant-based diets influence the insect herbivores' oral secretion (OS) composition and eventually the plant defense responses. We analyzed the OS composition of the generalist Lepidopteran insect, Helicoverpa armigera feeding on the host plant tomato (OSH), non-host plant capsicum (OSNH), and artificial diet (OSAD) using Liquid Chromatography-Quadrupole Time of Flight Mass Spectrometry. Higher numbers and levels of alkaloids and terpenoids were observed in OSH and OSNH, respectively while OSAD was rich in phospholipids. Interestingly, treatment of H. armigera OSAD, OSH and OSNH on wounded tomato leaves showed differential expression of (i) genes involved in JA and SA biosynthesis and their responsive genes, and (ii) biosynthetic pathway genes of chlorogenic acid (CGA) and trehalose, which exhibited increased accumulation along with several other plant defensive metabolites. Specifically, high levels of CGA were detected after OSH and OSNH treatments in tomato leaves. There was higher expression of the genes involved in phenyl-propanoid biosynthesis, which may lead to the increased accumulation of CGA and related metabolites. In the insect bioassay, CGA significantly inhibited H. armigera larval growth. Our results underline the differential accumulation of plant and insect OS metabolites and identified potential plant metabolite(s) affecting insect growth and development.
Keywords: Chlorogenic acid; defense; Metabolites; Non-host; Oral secretion; trehalose